Answer:
Step-by-step explanation:
Hello
A (5;2)
B (-1;-7)
y = ax + b
2 = 5a + b
-7 = -a + b
2 - (-7) = 5a - (-a) + b - b
2 + 7 = 5a + a
9 = 6a
a = 9/6
a = 3/2
2 = 3/2 * 5 + b
b = 2 - 15/2
b = 4/2 - 15/2
b = 11/2
y = 3/2 x + 11/2
y+1= 3/2(x-4)
y + 1 = 3/2 x - 6
y = 3/2 x - 6 - 1
y = 3/2 x - 7 => no
y-4= 3/2(x+1)
y - 4 = 3/2 x + 3/2
y = 3/2 x + 3/2 + 4
y = 3/2 x + 3/2 + 8/2
y = 3/2 x + 11/2 => yes
y+4= 3/2(x-1)
y + 4 = 3/2 x - 3/2
y = 3/2 x - 3/2 - 4
y = 3/2 x - 3/2 - 8/2
y = 3/2 x - 11/2 => no
y-1= 3/2 (x+4)
y - 1 = 3/2 x + 6
y = 3/2 x + 6 + 1
y = 3/2 x + 7 => no
Answer:
343 yd
Step-by-step explanation:
Answer:
The experimental probability of the outcome is 1/4
Step-by-step explanation:
-kitkat- i am going to say that every time lol
Answer: a) y=-29x-20 b) y=3/5x-18
Step-by-step explanation:
a) m = (-49-38)/(1 - (-2)) = -87/3 = -29
y=-29x+b --> Substitute (1,-49) as a point
(-49)=-29(1)+b
-49=-29+b
-b=-29+49
b=-20
Therefore, the equation of the line is y=-29x-20
b) m = (-18-(-9)/(0-15)) = -9/-15 = 3/5
The y-intercept is (0,-18) as it's where the line intersects the y-axis and x equals 0
Therefore, the equation of the line is y=3/5x-18
3x4=12 12x5=60 60x6=360 360x7=2,530 2,530x9=22,690